2023
DOI: 10.1101/2023.06.02.543307
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A fungal RNA-dependent RNA polymerase is a novel player in plant infection and cross-kingdom RNA interference

Abstract: Small RNAs act as fungal pathogen effectors that silence host target genes to promote infection, a virulence mechanism termed cross-kingdom RNA interference (RNAi). The essential pathogen factors of cross-kingdom small RNA production are largely unknown. We here characterized the RNA-dependent RNA polymerase (RDR)1 in the fungal plant pathogen Botrytis cinerea that is required for pathogenicity and cross-kingdom RNAi. B. cinerea bcrdr1 knockout (ko) mutants exhibited reduced pathogenicity and loss of cross-kin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The process where mobile sRNAs are transported between distantly related organisms leading to silencing the expression of target genes in the interacting partner through RNAi is known as crosskingdom RNAi (ckRNAi, Cai et al, 2018a) and has been described in plant and animal systems (Buck et al, 2014;Cai et al, 2019;Zhao et al, 2021) ckRNAi as a widespread defense strategy to suppress virulence targets in the invading organism (Zhang et al, 2016;Cai et al, 2018b;Hou et al, 2019;Zhu et al, 2022). Equally, evidences of sRNA movement from pathogens to plants, leading to the RNAi-mediated suppression of plant defense, pointed to ckRNAi as an evolutionarily conserved virulence mechanism (Weiberg et al, 2013;Wang et al, 2016;Xu et al, 2022;Cheng et al, 2023).…”
Section: Is There Cross-kingdom Rnai In the Am Symbiosis?mentioning
confidence: 99%
See 2 more Smart Citations
“…The process where mobile sRNAs are transported between distantly related organisms leading to silencing the expression of target genes in the interacting partner through RNAi is known as crosskingdom RNAi (ckRNAi, Cai et al, 2018a) and has been described in plant and animal systems (Buck et al, 2014;Cai et al, 2019;Zhao et al, 2021) ckRNAi as a widespread defense strategy to suppress virulence targets in the invading organism (Zhang et al, 2016;Cai et al, 2018b;Hou et al, 2019;Zhu et al, 2022). Equally, evidences of sRNA movement from pathogens to plants, leading to the RNAi-mediated suppression of plant defense, pointed to ckRNAi as an evolutionarily conserved virulence mechanism (Weiberg et al, 2013;Wang et al, 2016;Xu et al, 2022;Cheng et al, 2023).…”
Section: Is There Cross-kingdom Rnai In the Am Symbiosis?mentioning
confidence: 99%
“…In plants, numerous studies have confirmed ckRNAi as a widespread defense strategy to suppress virulence targets in the invading organism (Zhang et al ., 2016; Cai et al ., 2018b; Hou et al ., 2019; Zhu et al ., 2022). Equally, evidences of sRNA movement from pathogens to plants, leading to the RNAi‐mediated suppression of plant defense, pointed to ckRNAi as an evolutionarily conserved virulence mechanism (Weiberg et al ., 2013; Wang et al ., 2016; Xu et al ., 2022; Cheng et al ., 2023).…”
Section: Is There Cross‐kingdom Rnai In the Am Symbiosis?mentioning
confidence: 99%
See 1 more Smart Citation